(untitled) (Research, Society and Development, 2020)
Measurement of the benefits of ISO/TS 29001 standardization by companies that provide services and raw materials for companies that operate in oil segment, especially those that operate in the high seas, is the objective of this article, which deals especially with the case of a company which supplies lubricating fluid to vessels, demonstrating the specificities of this market by means of interviews with specialists and data collection.